1007Vitamin B6 intake, its active form pyridoxal 5'-phosphate, and markers of B6 activity and catabolism. (2nd September 2021) - Clasen, Joanna; Heath, Alicia K; Van Puyvelde, Heleen; Huybrechts, Inge; Johansson, Mattias; Ferrari, Pietro; Park, Jin Young; Brennan, Paul; Riboli, Elio; Muller, David C
Abstract: Background: Several biological pathways implicated in cancer risk rely on vitamin B6, which can be measured in its active form pyridoxal 5'-phosphate (PLP). Functional markers of B6 enzymatic activity have been proposed, including the homocysteine:cysteine ratio (Hcy:Cys, a marker of transsulfuration), 3-hydroxykynurenine ratio (HKr, a marker of tryptophan catabolism), and the 4-pyridoxic acid ratio (PAr, a marker of B6 catabolism). We investigated the extent to which these markers are associated with B6 intake. Methods: Data from 4, 750 participants in the European Prospective Investigation into Cancer and Nutrition (EPIC) study were included. We estimated the expected percentage change in each of the markers (PLP, Hcy:Cys, HKr, and PAr) for a doubling in B6 intake using log-linear Bayesian hierarchical regression models with log-transformed intake and biomarker data. Results: The percent change (posterior mean [95% Credible Interval (CrI)]) for a doubling of B6 intake was 61.0 [51.2, 71.8] for PLP, -12.7 [-15.2, -9.9] for Hcy:Cys, -12.9 [-15.7, -9.9] for HKr, and 1.3 [-3.5, 6.2] for PAr. Conclusions: B6 intake is most strongly associated with PLP, but is also associated with functional markers of transsulfuration and tryptophan catabolism, in the direction of increased activity in these pathways. There is no evidence of a linear association between vitamin B6 intake and catabolism. Key messages: Our results show differing sensitivity of PLP, markers of tryptophan catabolism and transsulfuration, and vitamin B6 catabolism to B6 intake.